2010
DOI: 10.4314/thrb.v12i4.52997
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial isolates and drug susceptibility patterns of urinary tract infection among pregnant women at Muhimbili National Hospital in Tanzania

Abstract: Urinary tract infection (UTI) during pregnancy may cause complications such as pyelonephritis 1%). Low rate to moderately high rate of antimicrobial drug resistance was observed against first line drugs namely, nitrofurantoin 18.7 % (n=16), co-trimoxazole 38.5 % (n=13) and ampicillin 57.7 % (n=26). Relatively low rate of resistance was seen against second line drugs: ciprofloxacin 13.6 % (n=22) and amikacin 5 % (n=20). High rate of resistance was observed in third generation cephalosporin cefotaxime 31.2 % (n=… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
35
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 23 publications
16
35
3
Order By: Relevance
“…(20; 22; 23). Echerichia coli was the most prevalent etiological agent in this study which agrees with the report of (22). The high rate of Escherichia coli infection could be attributed to its commensal nature in the intestinal tract and consequent faecal contamination due to poor hygiene.…”
Section: Resultssupporting
confidence: 91%
“…(20; 22; 23). Echerichia coli was the most prevalent etiological agent in this study which agrees with the report of (22). The high rate of Escherichia coli infection could be attributed to its commensal nature in the intestinal tract and consequent faecal contamination due to poor hygiene.…”
Section: Resultssupporting
confidence: 91%
“…In conformity with another previous study (21), Escherichia coli and Klebsiella pneumoniae were the predominantly isolated microorganisms. The other isolated bacteria include S. aureus, P. aeruginosa and Proteus species that are less common causes of UTI, unless if introduced iatrogenically (17,24).…”
Section: Discussionsupporting
confidence: 92%
“…The prevalence rates of 6.1-10.9% have been reported from Iran, 7.3% in Ghana and 13% -21% from Tanzania between 2009 and 2010 (9,21). A higher rate (55%) was reported from Nigeria (22).…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of asymptomatic bacteriuria does not change during pregnancy but there is change in pathogenesis, which keeps mother and baby at risk of complications due to urinary tract infection [1]. The prevalence proportion reported in this study ranged between 19.1% to 23.9% and agreed with studies done in Tanzania, Ibadan and sagamu which reported prevalence of 21.0%,21.0% and 23.9% respectively [18, 19]. This was however higher than a study done in Kano that found prevalence at 10.2% [20].…”
Section: Discussionsupporting
confidence: 85%